An Evaluation of the "Belia Di Jalan Raya" Road Safety Programme - Law, Teik Hua (1998)
In November 1996, a road safety programme known as the Belia di Jalan Raya road safety programme was carried out in Hulu Langat. The main objective of this programme was to reduce traffic accidents and injuries, especially among the motorcyclists.This thesis presents the impact of the one year safety programme in the Hulu Langat district. It provides an integrated approach to address accident problems by the enhancement of traffic enforcement, education and public information. The accident data were collected 23 months before and 12 months after the programme, in two comparison locations, Hulu Langat and Shah Alam. Shah Alam was used as a matched-pair control in this analysis. The Before and After analysis and the Box-Jenkins time series modeling technique were used to evaluate the effectiveness of the safety programme. Using the Before and After Chi-square test, it was found that the proportion of accidents in these two districts are Significantly different. This implies that the safety programme has a Significant effect on the reduction in the number of accidents, injuries and fatalities in Hulu Langat. The Box-Jenkins Time Series analysiS indicates an average reduction of 57 accidents, 8 hospitalized non-motorcyclist casualties, 15 non-motorcyclist fatalities, 18 hospitalized motorcyclists, 3 motorcyclist deaths, 3 young hospitalized non-motorcyclist casualties and 1 fatal motorcyclist in every month during the study period. In contrast, there had been an average increase in accidents and casualties in the comparison district, Shah Alam. The Survival Analysis shows that there was a significant improvement in overall traffic safety status in Hulu Langat after the implementation of the safety programme. In contrast, changes in traffic safety status in the comparison location, Shah Alam, did not resemble improvement in Hulu Langat in direction and magnitude.